Political economy of Malaysia - Moniruzzaman, Md. (Cengage Learning, 2013)
The chapter discusses the economic policies of development that the Malaysian government undertook since its independence in 1957. It describes the state intervention in economic policies that led to growth and industrialization. The policies were clearly counscious about economci, social and professional balance between the three major ethnic communities; and were adopted for phase-wise development towards full industrilization startign from primary products to manufactured export economy to heavy industrialization and knowledge economy.